ANTIDEPRESSANT EFFECTS OF FRESH JUICE, ETHYL ACETATE, AND N-HEXENE FRACTION OF UNRIPE AMBON BANANA PEELS ON MICE (MUS MUSCULUS) INDUCED BY UNPREDICTABLE CHRONIC MILD STRESS - SUHENDI, ANDI; PURUHITA, RANATRI; WAHYUNI, ARIFAH S. (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to determine the effects of fresh juice, ethyl acetate fraction, and n-hexene fraction of unripe Ambon banana peel as an antidepressant on mice (Mus musculus) and to determination of Brain-derived neurotrophic factor (BDNF) levels in the hippocampus. Methods: The animals weighing 20-30 g were induced stress by the UCMS (Unpredictable Chronic Mild Stress) method for five weeks with circadian disturbances, wet cages, wet bedding, empty cages, tilted cages, predator sounds, iced water, and restraints. Twenty-five mice were randomly divided into five groups, namely the negative control group (distilled water) for 15 days, and positive control group (Sertraline 9.1 mg/kg BW) for 15 days, fresh juice, ethyl acetate fraction, and n-hexene fraction of unripe Ambon banana peel were given 10 mg/kg BW for 15 days. Duration of immobility time with the FST and TST methods were measured. The brain organs histopathology was evaluated and BDNF protein expression was measured by Enzyme-Linked Immunosorbent Assay (ELISA). Results: Results showed that Fresh juice, ethyl acetate, and n-hexene fraction of unripe Ambon banana peel significantly reduced the immobility time (p<0.01) in the FST test by 56.63, 85.48, and 94.30 % and TST test, respectively, 57.16, 84.92, and 94.56%. Cell damage in the positive control group showed no significant difference with n-hexene fraction group (p = 0.098). BDNF expressed on groups positive, ethyl acetate, and n-hexene fractions. Meanwhile, negative control and fresh juice, BDNF proteins were unexpressed. Conclusion: n-hexane fraction has significant results with the positive control group on mice induced by mild chronic stress.